2010
DOI: 10.1088/0953-4075/43/4/045505
|View full text |Cite
|
Sign up to set email alerts
|

Zero absorption and a large negative refractive index in a left-handed four-level atomic medium

Abstract: In this paper, we have investigated three external fields interacting with the four-level atomic system described by the density-matrix approach. The atomic system exhibits left-handedness with zero absorption and large negative refractive index. Varying the parameters of the three external fields, the properties of zero absorption and large negative refractive index from the atomic system remain unvarying. Our scheme proposes an approach to obtain a negative refractive medium with zero absorption. The zero ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Due to the most essential applications in quantum information science, the optical characteristics of multi-level atomic systems and diverse configurations have also been addressed in detail [29][30][31][32][33][34][35][36][37][38]. Quantum coherence and interference have been shown in certain articles to cause the refractive index of a material to increase or even become negative [39][40][41][42]. Many approaches for realizing the high and negative refractive index in multi-level quantum systems have been proposed based on quantum interference [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the most essential applications in quantum information science, the optical characteristics of multi-level atomic systems and diverse configurations have also been addressed in detail [29][30][31][32][33][34][35][36][37][38]. Quantum coherence and interference have been shown in certain articles to cause the refractive index of a material to increase or even become negative [39][40][41][42]. Many approaches for realizing the high and negative refractive index in multi-level quantum systems have been proposed based on quantum interference [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, monolayer graphene's GH shifts features of transmitted and reflected beams with negative refractive indices have not yet been documented. Through various mechanisms, the circumstances that lead to negative refraction index for different media have been thoroughly researched [29][30][31][32][33][34]. In [33], large negative refractive index of four-level atomic medium with zero absorption have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [9] proposed a scheme for realization of the negative refractive index in a V-type fourlevel atomic system. Zhao et al [10]- [12] produced a negative refractive index with vanishing absorption in the four-level system and showed negative refraction can be controlled by an incoherent pump field. Zhang et al [13] showed the negative permittivity and the negative permeability of the medium can be achieved simultaneously in a wider frequency band in a closed V-type four-level dense atomic vapor.…”
Section: Introductionmentioning
confidence: 99%